2010
DOI: 10.1590/s0100-06832010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de bactérias promotoras de crescimento no abacaxizeiro cultivar Vitória durante a aclimatização

Abstract: Olivares (4),(1) Parte da Tese de Doutorado da primeira autora. Recebido em junho de 2009 e aprovado em janeiro de 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
25

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 30 publications
3
25
0
25
Order By: Relevance
“…Micropropagated plantlets with higher SDW and RDW are more vigorous and may exhibit better adaptation in later phases, since the more developed the root system, the higher the nutrient uptake and plant growth. The observed RDW results are in accordance with BALDOTTO et al (2010) andWEBER et al (2003), who observed positive effects in micropropagated pineapple plantlets when inoculated with diazotrophic bacteria. However, it is important to note that while the effects of diazotrophic bacteria on plant growth and nutrition may be associated mainly with biological N fixation, other mechanisms may also be involved, such as the biosynthesis of indoleacetic acid (IAA) (BALDOTTO et al,2010).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Micropropagated plantlets with higher SDW and RDW are more vigorous and may exhibit better adaptation in later phases, since the more developed the root system, the higher the nutrient uptake and plant growth. The observed RDW results are in accordance with BALDOTTO et al (2010) andWEBER et al (2003), who observed positive effects in micropropagated pineapple plantlets when inoculated with diazotrophic bacteria. However, it is important to note that while the effects of diazotrophic bacteria on plant growth and nutrition may be associated mainly with biological N fixation, other mechanisms may also be involved, such as the biosynthesis of indoleacetic acid (IAA) (BALDOTTO et al,2010).…”
Section: Resultssupporting
confidence: 91%
“…Some studies have been performed with the goal of improving the acclimatization of pineapple plantlets or testing the effects of different acclimatization times (BERILLI et al, 2011), foliar fertilization (BREGONCI et al, 2008), or inoculation with diazotrophic bacteria, which has been observed to positively affect the adaptation of pineapple plantlets to changes environments (BALDOTTO et al, 2010).…”
Section: Soil Sciencementioning
confidence: 99%
See 3 more Smart Citations